Atypical Thyrotoxic Psychosis with Seizure: A Case Report - B, Mohd Hayat; S, Syed Mushtaq; S, Smeena; US, Riyaz (IIUM Medical Journal Malaysia, 2012)
Thyrotoxicosis results in alteration in functioning of nervous system in some patients. However, these mental disturbances may be severe in rare cases in the form of manic-depressive, schizoid or paranoid reaction. The pathophysiological basis of these nervous system findings is not well understood.